Multi-stakeholders' preference for best management practices based on environmental awareness. (1st November 2019) - Du, Yi; Wang, Xiaoyan; Zhang, Lulu; Feger, Karl-Heinz; Popp, Jennie; Sharpley, Andrew
Abstract: Stakeholder participation is crucial in solving environmental problems, especially in rural areas. This research investigates multi-stakeholders environmental awareness and preferences for best management practices (BMPs) in water conservation zones of north China for tackling non-point source pollution issue. A sample of 287 stakeholders involving 62 environmental officials, 18 volunteers, 73 left-behind villagers, and 130 migrant workers were interviewed. New Ecological Paradigm (NEP) Scale and Principal component analysis were used to evaluate stakeholder's environmental awareness, preference for BMPs and factors influencing awareness and preference. Results show that engineering BMPs generally have a higher acceptance than management BMPs which can guide proper farming practices to reduce the likelihood of contamination from the source. Among the management measures, the preference for nutrient management was higher than that of tillage management. Considerable preference heterogeneity exists among different stakeholder groups in terms of BMPs in the case study area. Overall, environmental officials and volunteers are more supportive for implementing BMPs than left-behind farmers and migrant workers. In terms of implementation, environmental officials and volunteers tend to pay more attention to both the environmental benefit and economic benefit, while left-behind farmers and migrant workers focus more on economic benefit. To gain more economic benefit, people in areas with low economic levels are more willing to accept these measures to improve the status quo of living environment and income. Principal component analysis shows that demographics (23.6%), environmental awareness (15%), policies (13.6%) and economic (12.8%) can influence stakeholders' preference for BMPs. The cumulative contribution of the four factors accounts for 65%. The results suggest that decision makers need to coordinate multi-interest among the stakeholders and emphasize stakeholder consultation to meet local stakeholders' needs. We provide implications to policy-makers for revising existing or introducing adequate incentives to motivate local stakeholders and increase their support for implementing BMPs, instead of using enforcement.